(untitled) (BIRDEM Medical Journal, 2012)
Background and aim: This study was to evaluate atorvastatin in the management of hypercholesterolemia of cardiovascular risk patients as well as the implication of National Cholesterol Education Program (NCEP) Adult Treatment Panel (ATP) III guidelines in Bangladesh. Methods: A total 1685 patients aged 28 years or older who had evidence of hypercholesterolemia with or without Coronary Heart Diseases (CHD) and cardiovascular risk factors were assigned to receive atorvastatin for 2 months. The change of fasting LDL at baseline visit and after 2 months of the statin treatment was measured. Results: One thousand six hundred (95%) patients out of 1685 who were assigned to receive atorvastatin with TLC were found significant mean reduction (26.1%?) in their LDL levels from baseline visit. Triglycerides and total cholesterols were also reduced (16.6% ? and 21.6% ? respectively) wheras high-density lipoprotein was increased (16.5% ?) significantly. LDL of 23% patients was decreased more than 30 mg/dl after 2 months of atorvastatin treatment. Fifty nine percent of the patients reached the treatment goal of reducing LDL > 20 mg/dl. Conclusion: Atorvastatin would achieve a good effective control in the management of hypercholesterolemic patients with or without CHD and risk factors following the guidelines of US NCEP ATP III. DOI: http://dx.doi.org/10.3329/birdem.v2i1.12354 Birdem Med J 2012; 2(1) 5-13